Improving Water Use Efficiency of Rice-Wheat Cropping System by Adopting Micro-Irrigation Systems - Meena, Raj Pal; Sharma, R. K.; Chhokar, R. S.; Chander, Subhash; Tripathi, S. C.; Kumar, Raj; Sharma, Indu (International Journal of Bio-resource and Stress Management, 2015)
Rice-wheat is the predominant cropping system and contributes more than 70% of food grain production in India. However, major problem in this system is depletion and deterioration of water resources. Therefore, efforts must be focussed on reversing the trend in water resources depletion by adopting efficient irrigation technologies. The prevalent irrigation methods are less efficient due to more water losses through leaching and evaporation. Micro irrigation can be an effective tool for improving water use efficiency. The study was carried out with an objective of improving the WUE in rice-wheat cropping system with four irrigation methods in wheat crop viz check basin, drip, sprinkler and drip+rainport and three irrigation systems in rice (check basin, drip and sprinkler) at Indian Institute of Wheat and Barley Research, Karnal during 2012-13 and 2013-14. Irrigation treatments significantly affected the grain yield of both the crops. The highest grain yield of wheat (5752 kg ha-1) was obtained in check basin irrigation during 2012-13 followed by drip+rainport (5614 kg ha-1). However, the WUE of check basin method was minimum (1.32 kg m-3). During 2013-14, highest yield was obtained in drip+rainport (5545 kg ha-1) followed by drip irrigation (5475 kg ha-1) with the WUE of 1.57 and 1.55 kg m-3 respectively. In rice, significant higher grain yield (4028 and 4683 kg ha-1) was recorded in drip followed by sprinkler irrigation. The study concludes the maximum WUE in wheat under drip+rainport treatment and in rice it was under drip irrigation treatment.